User Interface & User Experience Design of the BangSatria Joki Website Using the Design Thinking Method - Rio Fawwaz Helmi (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2026)
The rapid growth of the online gaming industry has created various new economic opportunities, one of which is game boosting services. However, many platforms offering such services have not yet optimized their user interface (UI) and user experience (UX) design, resulting in poor user comfort and trust. This study aims to design the UI and UX of the BangSatria Joki website as a platform for game boosting services by applying the Design Thinking method. The Design Thinking approach consists of five stages: Empathize, Define, Ideate, Prototype, and Testing. The initial stages involved observing competitor websites and conducting interviews with potential users to identify their needs and challenges. The analysis results were then translated into user personas, brainstorming, mind mapping, and wireframe designs. A high-fidelity prototype was then developed using Figma. In the testing phase, the System Usability Scale (SUS) was used to evaluate user satisfaction with the design. Based on tests conducted with 57 student respondents, the website prototype received a SUS score of 78.9, indicating an